Collective criminality and sexual violence: Fixing a failed approach - SáCouto, Susana; Sadat, Leila Nadya; Sellers, Patricia Viseur (Leiden journal of international law, 2020)
International criminal tribunals have developed a number of legal theories designed to hold individuals responsible for their role in collective criminal conduct. These doctrines of criminal participation, known as modes of liability, are the subject of significant scholarly commentary. Yet missing from much of this debate, particularly as regards the International Criminal Court, has been an analysis of how current doctrine on modes of liability responds to the need to hold collective perpetrators criminally responsible for crimes of sexual and gender-based violence (SGBV). Indeed, many writings in this area of the law address perceived shortcomings in the theoretical underpinnings of modes of liability doctrine in the abstract but ignore the application of this doctrine in concreto . As a result, facially neutral writings on modes of liability may in fact be gendered in application, either because they fail to account for the specific characteristics of sexual and gender-based violence or because they are applied in a manner that requires higher thresholds for finding culpability for the commission of SGBV crimes. This article fills the gap between theory and practice, examining past and present doctrine, and suggesting ways in which the treatment of modes of liability by international criminal courts and tribunals can both properly respond to the need for personal culpability and the dangers of collective criminal activity, particularly as regards SGBV crimes.